MEDIA ALTERNATIF EKSTRAK UBI JALAR SEBAGAI MEDIA TUMBUH JAMUR Aspergillus sp dan Candida sp PADA SERUMEN TELINGA PETANI DI KELURAHAN DORPEDU KOTA TERNATE - Mukhtasyam Zuchrullah; Erpi Nurdin; Rahmawati Puni (Universitas Patompo, 2023)
Fungal are plants that require habitat conditions and high humidity. So it is one of the causes of public health problems in Indonesia. Groups at high risk of fungal infection are farmers because one of them is in direct contact with warm and humid areas at work. Otomycosis is a fungal infection that often occurs in the outer ear. Predisposing factors that influence include high humidity, local trauma which is often caused by the habit of using cotton buds, iron hooks and hair strands, long-term use of steroids and a history of dermatomycosis. Otomycosis is one of the common symptoms that are often found in ENT clinics and its prevalence reaches 9% of all patients who show symptoms and signs of otitis externa with Candida Sp and Aspergillus as the fungal species obtained the most from the oscillates. This study aims to determine the presence of fungal growth in the ear serum of farmers in Dorpedu Village. The location of the sampling was conducted in the Dorpedu Village, Ternate City and the location of this research was carried out at the Integrated Laboratory of the Health Polytechnic of the Ministry of Health of Ternate, Department of Medical Laboratory Technology. The method used in this study is to examine the culture and followed by 10% KOH staining. This study used accidental sampling technique with a sample of 20 farmers' ear serumThe results obtained showed that from 20 samples of farmers' ear serum in Dorpedu Village examined, Candida albicans and Aspergillus sp.: Based on the results of the research conducted, it can be seen that from 20 samples of farmer ear serum in Dorpedu Village, it was found that in the sweet potato extract media there were 17 (85%) positive samples of C. albicans, 1 (5%)positive samples of Aspergillus sp. PDA 20 (100%) samples were positive for C. albicans, and 2 (10%) samples were negative on sweet potato extract media where no fungal colonies were found. Sweet potato extract media can be used as an alternative medium for fungal growth.Keywords: Fungal, ear cerumen swab, otomycosis